Peningkatan Kualitas Gambar pada Sistem Streaming Video Menggunakan Teknik Kompresi Citra - Wiguna, I Made Sastra; Santiyasa, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025DO - 10.24843/JNATIA.2025.v03.i02.p20, 2025)
This research aims to enhance the quality of images in video streaming systems by utilizing image compression techniques. Although image compression techniques have become standard in reducing image file sizes, they often result in significant quality degradation. In the context of video streaming systems, where image quality is paramount, this challenge becomes increasingly prominent. Therefore, in this study, we propose an approach that integrates image compression techniques with detail recovery methods to improve the quality of images transmitted through video streaming systems. Experiments were conducted to evaluate the effectiveness of the proposed approach in enhancing image quality, with results showing a significant improvement compared to conventional approaches.